Foliar water uptake: Processes, pathways, and integration into plant water budgets. (9th October 2018) - Berry, Z. Carter; Emery, Nathan C.; Gotsch, Sybil G.; Goldsmith, Gregory R.
Abstract: Nearly all plant families, represented across most major biomes, absorb water directly through their leaves. This phenomenon is commonly referred to as foliar water uptake. Recent studies have suggested that foliar water uptake provides a significant water subsidy that can influence both plant water and carbon balance across multiple spatial and temporal scales. Despite this, our mechanistic understanding of when, where, how, and to what end water is absorbed through leaf surfaces remains limited. We first review the evidence for the biophysical conditions necessary for foliar water uptake to occur, focusing on the plant and atmospheric water potentials necessary to create a gradient for water flow. We then consider the different pathways for uptake, as well as the potential fates of the water once inside the leaf. Given that one fate of water from foliar uptake is to increase leaf water potentials and contribute to the demands of transpiration, we also provide a quantitative synthesis of observed rates of change in leaf water potential and total fluxes of water into the leaf. Finally, we identify critical research themes that should be addressed to effectively incorporate foliar water uptake into traditional frameworks of plant water movement. Abstract : Despite being represented across numerous plant families and providing a notable water subsidy to plants, the process of foliar water uptake is still poorly understood. This review addresses the need for a cohesive synthesis of the processes that drive foliar uptake, the pathways of water movement, and the role of this water in plant water budgets. In addition to these components, we address the critical knowledge gaps needed for a more complete understanding of this nearly ubiquitous process.